2013
DOI: 10.5935/01012800.20130004
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of vitamin D and chronic periodontitis in patients with chronic kidney disease

Abstract: In patients with CKD not yet on dialysis, vitamin D deficiency is associated with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…The interaction between molecular patterns of certain periodontopathic bacteria and TLR1/2 of innate oral immunocytes including monocytes/macrophages and keratinocytes may also induce the expression of VDR and the production of 1,25(OH) 2 D by these cells. In turn, the 1,25(OH) 2 D/VDR signalling induces the expression of genes encoding the antibacterial agents cathelicidin and β defencin [ 1 , 10 , 51 ] which may provide some protection against the development of bacterial plaque-induced chronic periodontitis [ 13 ].…”
Section: Periodontitismentioning
confidence: 99%
See 3 more Smart Citations
“…The interaction between molecular patterns of certain periodontopathic bacteria and TLR1/2 of innate oral immunocytes including monocytes/macrophages and keratinocytes may also induce the expression of VDR and the production of 1,25(OH) 2 D by these cells. In turn, the 1,25(OH) 2 D/VDR signalling induces the expression of genes encoding the antibacterial agents cathelicidin and β defencin [ 1 , 10 , 51 ] which may provide some protection against the development of bacterial plaque-induced chronic periodontitis [ 13 ].…”
Section: Periodontitismentioning
confidence: 99%
“…In progressive chronic periodontitis, dissemination of periodontopathic bacteria and of inflammatory mediators from the inflamed periodontal tissues is not uncommon. As a result, in a subset of genetically predisposed persons with upregulated immunoinflammatory responses, active chronic periodontitis can increase the risk of cardiovascular disease, stroke, inadequate glycaemic control in diabetes mellitus, and complications of pregnancy [ 1 , 4 ]. Indeed, it has been reported that after adjustment for confounding variables, compared to those with minimal periodontal disease, subjects with advanced periodontitis have a 25% increased risk of coronary heart disease [ 4 ].…”
Section: Periodontitismentioning
confidence: 99%
See 2 more Smart Citations
“…[ 21 ] Several recent reports demonstrate a significant association between periodontal health and the intake of Vitamin D. Evidence has demonstrated that Vitamin D might be beneficial for oral health, not only for its direct positive effect on bone health and mineral metabolism but also due to its indirect action as an anti-inflammatory agent. [ 22 23 24 ]…”
Section: Introductionmentioning
confidence: 99%